Weather-resistant high-strength anti-corrosion rust remover based on inorganic composite material, preparation method and application to bolt
By using inorganic composite materials to prepare high-strength anti-corrosion and rust removers in rust coatings, the shortcomings of existing coatings in weather resistance are solved, and coatings with high mechanical strength and long-lasting weather resistance and corrosion resistance are achieved, which are suitable for bolts and other applications.
Patent Information
- Application Number
- CN202510156928.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-13
- Publication Date
- 2025-04-22
AI Technical Summary
Existing rust-resistant coatings have shortcomings in improving the material's light resistance and other weather resistance, which limits the application of materials.
A weather-resistant high-strength anti-corrosion rust remover based on inorganic composite materials is used. This rust remover forms a coating with excellent anti-corrosion weather resistance by preparing hydrotalcite/block copolymer composite material and phosphorus-containing epoxy acrylate, combined with methyl gallate acrylate and a photoinitiator.
The formed coating has high mechanical strength and lasting weather-resistant and corrosion-resistant properties, which is suitable for the corrosion protection of bolts, significantly improving the UV aging resistance, weather-resistant and mechanical properties of the coating.
Smart Images

Figure CN119859459A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coatings, and in particular to a weather-resistant high-strength anticorrosion and rust remover based on an inorganic composite material, a preparation method and application of the same on bolts. Background Art
[0002] Rust-resistant paint, also known as low surface treatment paint, refers to a type of paint that can be applied on steel surfaces that have not been fully rust-removed and still has good anti-rust properties. Its working principle is to convert or passivate active and harmful rust into stable substances, which adhere to the surface of the metal substrate to form a protective layer, thereby achieving the purpose of long-term protection of the substrate and corrosion inhibition.
[0003] Rust-resistant paints are generally divided into three types: stable, penetrating, and conversion types. Stable rust-resistant paints mainly rely on the active pigments and rust stabilizers in the system to form stable and insoluble heteropolyacid complexes with active rust to achieve the purpose of rust stabilization and corrosion protection; penetrating rust-resistant paints generally do not react with rust, and mainly use permeable resins to seal and adhere rust to the surface of the substrate through wetting and penetration to prevent erosion by external corrosive media and to prevent the electrochemical reaction between rust and the substrate from continuing; the conversion agent in conversion rust-resistant paints can convert rust substances into coordination compounds that are passivated, harmless, or have a certain protective effect, and then use film-forming substances to adhere the converted products to the substrate to form a complete passivation protective coating.
[0004] Existing technologies such as Chinese patent CN109181452A disclose a conversion type water-based rust-resistant paint and its preparation method, which adds corrosion inhibitors, tannic acid, stabilizers and other additives to the modified acrylic copolymer emulsion to make the conversion type water-based rust-resistant paint have excellent adhesion, impact resistance and corrosion resistance, and can be directly applied to the surface of rusted steel. However, the paint is not good at improving the weather resistance of the material, such as light resistance, which limits the application of the material. Summary of the invention
[0005] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a weather-resistant, high-strength anti-corrosion and rust remover based on an inorganic composite material, a preparation method and an application on bolts. The rust remover has excellent anti-corrosion and weather-resistant properties. As a rust-bearing coating, after being coated and cured on the surface of an incompletely rusted substrate, a passivation protective coating is formed. The coating has high mechanical strength and long-lasting weather-resistant and anti-corrosion properties, and can be used for the anti-corrosion protection of bolts.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is as follows:
[0007] A method for preparing a weather-resistant high-strength anticorrosion and rust remover based on an inorganic composite material comprises the following steps:
[0008] Step (1), preparing a hydrotalcite / block copolymer composite material;
[0009] S11, mixing thieno[3,4-B]-1,4-dioxin-2-methanol, tetrahydrofuran and sodium hydride uniformly, adding 1,4-di(bromomethyl)benzene, reacting, cooling after the reaction, purifying, and obtaining a thiophene-containing initiator;
[0010] S12, mixing cuprous bromide, pentamethyldiethylenetriamine, styrene and dimethyl sulfoxide evenly, reacting, adding a hydrotalcite dispersion and a thiophene-containing initiator, and continuing the reaction, purifying, and obtaining a hydrotalcite / block copolymer composite material after the reaction is completed;
[0011] Step (2), mixing bisphenol A epoxy resin, hydroquinone and tetraethylammonium bromide uniformly, adding di(methacryloyloxyethyl) hydrogen phosphate, reacting, and obtaining phosphorus-containing epoxy acrylate after the reaction is completed;
[0012] Phosphorus-containing epoxy acrylate, methyl gallate acrylate, active diluent and photoinitiator are uniformly mixed, and hydrotalcite / block copolymer composite material is added and ultrasonically dispersed to obtain a weather-resistant and high-strength anticorrosion and rust remover based on an inorganic composite material.
[0013] Preferably, in S11 of step (1), the mass ratio of thieno[3,4-B]-1,4-dioxin-2-methanol, tetrahydrofuran and sodium hydride is 6.2-6.3:50-60:2.1-2.2; the molar ratio of thieno[3,4-B]-1,4-dioxin-2-methanol and 1,4-di(bromomethyl)benzene is 1:1.1-1.2; and the reaction conditions are: reacting in a nitrogen atmosphere at a set temperature of 65-75°C for 8-10h.
[0014] Preferably, the purification operation is as follows: taking the reaction product obtained after cooling to room temperature, adding ethyl acetate and water in an amount 3-4 times the mass of the reaction product in sequence for extraction, taking the organic phase, adding 20wt% anhydrous magnesium sulfate of the organic phase to dry and remove water, filtering, taking the filtrate, removing the solvent ethyl acetate by rotary evaporation at a temperature of 50-60°C, and separating by column chromatography.
[0015] Furthermore, the eluent used in the column chromatography separation is prepared by mixing n-hexane and ethyl acetate in a volume ratio of 10:1.
[0016] Preferably, in S12 of step (1), the mass ratio of cuprous bromide, pentamethyldiethylenetriamine, styrene, dimethyl sulfoxide, hydrotalcite dispersion and thiophene-containing initiator is 0.5-0.6:0.6-0.7:4-6:45-50:240-260:4-6; the reaction conditions are: reacting in a nitrogen atmosphere at a temperature of 80-85°C; and the continued reaction conditions are: continuing the reaction in a nitrogen atmosphere at a temperature of 80-85°C for 2-3h.
[0017] Preferably, the hydrotalcite dispersion in S12 of step (1) is prepared by the following steps: mixing acrylic acid, hydrotalcite and dimethyl sulfoxide in a mass ratio of 2-3:10:100-130, and ultrasonically dispersing to obtain a hydrotalcite dispersion.
[0018] Preferably, the purification operation comprises: taking the crude reaction product obtained after the reaction is completed, adding methanol 5-6 times the mass of the crude reaction product, standing for 10-15 minutes, filtering, taking the filter cake, adding dichloromethane and water 5-6 times the mass of the filter cake in turn for washing, and drying at 50-60° C. for 12-18 hours.
[0019] Preferably, in step (2), the mass ratio of bisphenol A epoxy resin, hydroquinone and tetraethylammonium bromide is 100:0.025-0.03:0.4-0.5; the molar ratio of bisphenol A epoxy resin to di(methacryloyloxyethyl) hydrogen phosphate is 1:2; and the reaction conditions are: reacting at a temperature of 70-80°C for 4-5h.
[0020] Preferably, the addition temperature of the di(methacryloyloxyethyl) hydrogen phosphate is 50-60°C.
[0021] Preferably, in step (2), the mass ratio of phosphorus-containing epoxy acrylate, methyl gallate acrylate, reactive diluent, photoinitiator, and hydrotalcite / block copolymer composite material is 70-75:5-6:15-20:3-4:4-5.
[0022] Preferably, in step (2), methyl gallate of acrylic acid is prepared by the following steps:
[0023] Mix and dissolve methyl gallate, triethylamine and acetone, add acryloyl chloride dropwise, and after the addition is complete, heat and react. After the reaction is complete, filter and purify to obtain methyl gallate of acrylic acid;
[0024] Among them, the mass ratio of methyl gallate, triethylamine and acetone is 3.5-3.7:0.5:40-50; the molar ratio of methyl gallate to acryloyl chloride is 1:1-1.1; the dripping conditions of acryloyl chloride are: dripping for 20-30 minutes at 0-2°C in a nitrogen atmosphere; the reaction conditions are: reacting at 35-40°C for 5-6 hours.
[0025] Preferably, the purification operation comprises: taking the filtrate after filtration, removing the solvent acetone by rotary evaporation at a temperature of 30-40°C to obtain a crude reaction product, adding 0°C water with a mass of 5-8 times that of the crude reaction product for washing, and drying at a temperature of 50-60°C for 10-12h.
[0026] Preferably, a weather-resistant and high-strength anti-corrosion and rust-removing agent based on an inorganic composite material is prepared by the preparation method of the weather-resistant and high-strength anti-corrosion and rust-removing agent based on an inorganic composite material as described above.
[0027] Preferably, an application of the weather-resistant high-strength anti-corrosion and rust remover based on the inorganic composite material as described above is used on bolts.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] Hydrotalcite materials are a type of layered compounds composed of negatively charged anions and positively charged metal hydroxides, also known as layered double metal hydroxides. The interlayer anions are exchangeable, and anion-containing compounds can be inserted into the interlayers of hydrotalcite to form composite materials. The present invention uses acrylic acid to intercalate hydrotalcite, and uses an in-situ polymerization method to prepare a hydrotalcite / block copolymer composite material. The thiophene-containing initiator in the present invention is prepared by reacting the phenolic hydroxyl group on thieno[3,4-B]-1,4-dioxin-2-methanol with an excess of 1,4-di(bromomethyl)benzene by nucleophilic substitution, and can undergo an atom transfer free radical polymerization reaction with acrylic acid and styrene between hydrotalcite layers to form a block copolymer, which not only improves the dispersibility and compatibility of the inorganic filler hydrotalcite in the matrix, but also, due to the heterocyclic structure of the thiophene group, can use lone pairs of electrons to form coordination bonds with iron ions in rust and iron on the surface of the iron-containing metal substrate, so that the prepared hydrotalcite / block copolymer composite material can be used as a corrosion inhibitor to give the coating matrix excellent anti-corrosion performance;
[0030] In addition, since hydrotalcite is an inorganic reinforcing filler with a layered structure and excellent ultraviolet absorption properties, the maze effect when it is dispersed in the coating increases the diffusion path of the corrosive medium to the metal surface, prolongs the corrosion resistance time, and further improves the coating's anti-corrosion performance. At the same time, the coating's resistance to ultraviolet aging, weather resistance, and mechanical properties are also improved.
[0031] Epoxy resin has excellent chemical resistance and good adhesion. Combining it with the advantages of acrylic resin such as good weather resistance, the epoxy acrylate prepared can be cured into a film under ultraviolet light irradiation conditions. The paint film has a high cross-linking density, adheres tightly to the metal surface, and has excellent anti-corrosion properties. The present invention uses di(methacryloyloxyethyl) hydrogen phosphate to end-cap bisphenol A epoxy resin to form a phosphorus-containing epoxy acrylate containing unsaturated carbon-carbon double bonds and phosphate functional groups. It is used as a base material for the coating and mixed with a hydrotalcite / block copolymer composite material, methyl gallate of acrylic acid, an active diluent, and a photoinitiator to form a weather-resistant, high-strength anti-corrosion and rust remover based on an inorganic composite material;
[0032] Among them, phosphorus-containing epoxy acrylate contains phosphate functional groups that can chelate iron ions, which improves the mechanical properties and adhesion of the coating, and has excellent flash corrosion resistance and anti-corrosion properties; methyl acrylate gallate is prepared by an esterification reaction between the phenolic hydroxyl group of methyl gallate and acryloyl chloride. While participating in the photocuring of the matrix resin, it utilizes the strong chelating ability of the phenolic hydroxyl group with iron ions to form a structurally stable complex with the iron ions. As a rust conversion agent, it cooperates with phosphorus-containing epoxy acrylate and hydrotalcite / block copolymer composite materials to play the role of rust conversion, shielding and corrosion inhibition, thereby improving the anti-corrosion performance of the coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 It is a process flow chart for preparing a weather-resistant high-strength anticorrosion and rust remover based on an inorganic composite material in the present invention;
[0034] Figure 2 is a schematic diagram of the reaction for preparing a thiophene-containing initiator in the present invention;
[0035] Figure 3 It is a bar graph of the impact strength of samples 1-8 in the comprehensive performance test of the present invention. DETAILED DESCRIPTION
[0036] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0037] Example 1
[0038] This embodiment discloses a method for preparing a weather-resistant high-strength anticorrosion and rust remover based on an inorganic composite material, comprising the following steps:
[0039] Step (1), preparing a hydrotalcite / block copolymer composite material;
[0040] S11, thieno[3,4-B]-1,4-dioxin-2-methanol, tetrahydrofuran, and sodium hydride were mixed in a nitrogen atmosphere at a mass ratio of 6.2:50:2.1, 1,4-di(bromomethyl)benzene was added, and the molar ratio of thieno[3,4-B]-1,4-dioxin-2-methanol to 1,4-di(bromomethyl)benzene was 1:1.1, and the reaction was carried out at a set temperature of 65°C for 10 hours. After the reaction was completed, the reaction was cooled to room temperature to obtain a reaction product, and ethyl acetate and water in an amount of 3 times the mass of the reaction product were added in sequence for extraction, the organic phase was taken, 20 wt% of anhydrous magnesium sulfate was added to the organic phase for drying and dehydration, the organic phase was filtered, the filtrate was taken, the solvent ethyl acetate was removed by rotary evaporation at 50°C, and the thiophene-containing initiator was obtained;
[0041] The eluent used in column chromatography separation was prepared by mixing n-hexane and ethyl acetate in a volume ratio of 10:1;
[0042] S12, mixing acrylic acid, hydrotalcite and dimethyl sulfoxide in a mass ratio of 2:10:100, and ultrasonically dispersing for 10 minutes to obtain a hydrotalcite dispersion;
[0043] Cuprous bromide, pentamethyldiethylenetriamine, styrene and dimethyl sulfoxide were mixed evenly, reacted in a nitrogen atmosphere at 80°C, and after the reaction was completed, a hydrotalcite dispersion and a thiophene-containing initiator were added, and the reaction was continued for 3 hours in a nitrogen atmosphere at 80°C. After the reaction was completed, a crude reaction product was obtained, methanol 5 times the mass of the crude reaction product was added, and the mixture was allowed to stand for 10 minutes, filtered, and the filter cake was taken. Dichloromethane 5 times the mass of the filter cake and water were added in turn for washing, and the mixture was dried at 50°C for 18 hours to obtain a hydrotalcite / block copolymer composite material;
[0044] The mass ratio of cuprous bromide, pentamethyldiethylenetriamine, styrene, dimethyl sulfoxide, hydrotalcite dispersion, and thiophene-containing initiator is 0.5:0.6:4:45:240:4;
[0045] Step (2), bisphenol A epoxy resin, hydroquinone, and tetraethylammonium bromide are uniformly mixed in a mass ratio of 100:0.025:0.4, di(methacryloyloxyethyl) hydrogen phosphate is added at a temperature of 50° C., the molar ratio of bisphenol A epoxy resin to di(methacryloyloxyethyl) hydrogen phosphate is 1:2, and the reaction is carried out at a temperature of 70° C. for 5 hours. After the reaction is completed, phosphorus-containing epoxy acrylate is obtained;
[0046] Phosphorus-containing epoxy acrylate, methyl gallate of acrylate, active diluent and photoinitiator are uniformly mixed, and hydrotalcite / block copolymer composite material is added, and ultrasonic dispersion is performed at 40° C. for 30 minutes to obtain a weather-resistant and high-strength anticorrosion and rust remover based on an inorganic composite material;
[0047] The mass ratio of phosphorus-containing epoxy acrylate, methyl gallate acrylate, reactive diluent, photoinitiator, and hydrotalcite / block copolymer composite material is 70:5:15:3:4;
[0048] Methyl gallate of acrylic acid is prepared by the following steps:
[0049] Methyl gallate, triethylamine and acetone were mixed and dissolved in a mass ratio of 3.5:0.5:40, and acryloyl chloride was added dropwise in a nitrogen atmosphere at 0°C, the molar ratio of methyl gallate to acryloyl chloride was 1:1, and the dropping time was 20 min. After the dropping was completed, the temperature was raised to 35°C and reacted for 6 h. After the reaction was completed, the filtrate was filtered and the solvent acetone was removed by rotary evaporation at 30°C to obtain a crude reaction product. 0°C water with an amount 5 times the mass of the crude reaction product was added for washing, and the product was dried at 50°C for 12 h to obtain methyl gallate of acrylic acid.
[0050] Example 2
[0051] This embodiment discloses a method for preparing a weather-resistant high-strength anticorrosion and rust remover based on an inorganic composite material, comprising the following steps:
[0052] Step (1), preparing a hydrotalcite / block copolymer composite material;
[0053] S11, thieno[3,4-B]-1,4-dioxin-2-methanol, tetrahydrofuran, and sodium hydride were mixed in a nitrogen atmosphere at a mass ratio of 6.23:55:2.15, 1,4-di(bromomethyl)benzene was added, and the molar ratio of thieno[3,4-B]-1,4-dioxin-2-methanol to 1,4-di(bromomethyl)benzene was 1:1.1, and the reaction was carried out at a set temperature of 70°C for 9 hours. After the reaction was completed, the reaction was cooled to room temperature to obtain a reaction product, and ethyl acetate and water were added in an amount of 3 times the mass of the reaction product to extract the product, and the organic phase was taken, and 20 wt% of anhydrous magnesium sulfate was added to the organic phase to dry and remove water, and the filtrate was taken, and the solvent ethyl acetate was removed by rotary evaporation at 50°C, and the thiophene-containing initiator was obtained by column chromatography;
[0054] The eluent used in column chromatography separation was prepared by mixing n-hexane and ethyl acetate in a volume ratio of 10:1;
[0055] S12, mixing acrylic acid, hydrotalcite and dimethyl sulfoxide in a mass ratio of 2.3:10:120, and ultrasonically dispersing for 10 minutes to obtain a hydrotalcite dispersion;
[0056] Cuprous bromide, pentamethyldiethylenetriamine, styrene and dimethyl sulfoxide were mixed evenly, reacted in a nitrogen atmosphere at 80°C, and after the reaction was completed, a hydrotalcite dispersion and a thiophene-containing initiator were added, and the reaction was continued for 2 hours in a nitrogen atmosphere at 80°C. After the reaction was completed, a crude reaction product was obtained, methanol 5 times the mass of the crude reaction product was added, and the mixture was allowed to stand for 10 minutes, filtered, and the filter cake was taken, and dichloromethane 5 times the mass of the filter cake and water were added in turn for washing, and dried at 50°C for 18 hours to obtain a hydrotalcite / block copolymer composite material;
[0057] The mass ratio of cuprous bromide, pentamethyldiethylenetriamine, styrene, dimethyl sulfoxide, hydrotalcite dispersion, and thiophene-containing initiator is 0.53:0.63:4.5:48:245:4.5;
[0058] Step (2), bisphenol A epoxy resin, hydroquinone, and tetraethylammonium bromide are mixed uniformly in a mass ratio of 100:0.025:0.4, di(methacryloyloxyethyl) hydrogen phosphate is added at a temperature of 55° C., the molar ratio of bisphenol A epoxy resin to di(methacryloyloxyethyl) hydrogen phosphate is 1:2, and the reaction is carried out at a temperature of 75° C. for 4.5 hours. After the reaction is completed, phosphorus-containing epoxy acrylate is obtained;
[0059] Phosphorus-containing epoxy acrylate, methyl gallate acrylate, active diluent and photoinitiator are uniformly mixed, and hydrotalcite / block copolymer composite material is added, and ultrasonic dispersion is performed at 40° C. for 25 minutes to obtain a weather-resistant and high-strength anticorrosion and rust remover based on an inorganic composite material;
[0060] The mass ratio of phosphorus-containing epoxy acrylate, methyl gallate acrylate, reactive diluent, photoinitiator, and hydrotalcite / block copolymer composite material is 72:5.3:16:3.5:4.3;
[0061] Methyl gallate of acrylic acid is prepared by the following steps:
[0062] Methyl gallate, triethylamine and acetone were mixed and dissolved in a mass ratio of 3.55:0.5:45, and acryloyl chloride was added dropwise in a nitrogen atmosphere at 0°C, the molar ratio of methyl gallate to acryloyl chloride was 1:1, and the addition time was 25 min. After the addition was completed, the temperature was raised to 35°C and the reaction was carried out for 5.5 h. After the reaction was completed, the filtrate was filtered and the solvent acetone was removed by rotary evaporation at 30°C to obtain a crude reaction product. 0°C water with an amount 5 times the mass of the crude reaction product was added for washing, and the product was dried at 50°C for 12 h to obtain methyl gallate of acrylic acid.
[0063] Example 3
[0064] This embodiment discloses a method for preparing a weather-resistant high-strength anticorrosion and rust remover based on an inorganic composite material, comprising the following steps:
[0065] Step (1), preparing a hydrotalcite / block copolymer composite material;
[0066] S11, thieno[3,4-B]-1,4-dioxin-2-methanol, tetrahydrofuran, and sodium hydride were mixed in a nitrogen atmosphere at a mass ratio of 6.25:55:2.15, 1,4-di(bromomethyl)benzene was added, and the molar ratio of thieno[3,4-B]-1,4-dioxin-2-methanol to 1,4-di(bromomethyl)benzene was 1:1.15, and the reaction was carried out at a set temperature of 70°C for 9 hours. After the reaction was completed, the reaction was cooled to room temperature to obtain a reaction product, and ethyl acetate and water in an amount of 3 times the mass of the reaction product were added in sequence for extraction, the organic phase was taken, 20 wt% of anhydrous magnesium sulfate was added to the organic phase for drying and dehydration, the organic phase was filtered, the filtrate was taken, the solvent ethyl acetate was removed by rotary evaporation at 50°C, and the thiophene-containing initiator was obtained;
[0067] The eluent used in column chromatography separation was prepared by mixing n-hexane and ethyl acetate in a volume ratio of 10:1;
[0068] S12, mixing acrylic acid, hydrotalcite and dimethyl sulfoxide in a mass ratio of 2.5:10:120, and ultrasonically dispersing for 10 minutes to obtain a hydrotalcite dispersion;
[0069] Cuprous bromide, pentamethyldiethylenetriamine, styrene and dimethyl sulfoxide were mixed evenly, reacted in a nitrogen atmosphere at 80°C, and after the reaction was completed, a hydrotalcite dispersion and a thiophene-containing initiator were added, and the reaction was continued for 2 hours in a nitrogen atmosphere at 85°C. After the reaction was completed, a crude reaction product was obtained, methanol 5 times the mass of the crude reaction product was added, and the mixture was allowed to stand for 10 minutes, filtered, and the filter cake was taken, and dichloromethane 5 times the mass of the filter cake and water were added in turn for washing, and dried at 50°C for 18 hours to obtain a hydrotalcite / block copolymer composite material;
[0070] The mass ratio of cuprous bromide, pentamethyldiethylenetriamine, styrene, dimethyl sulfoxide, hydrotalcite dispersion, and thiophene-containing initiator is 0.55:0.65:5:48:250:5;
[0071] Step (2), bisphenol A epoxy resin, hydroquinone, and tetraethylammonium bromide are uniformly mixed in a mass ratio of 100:0.025:0.45, di(methacryloyloxyethyl) hydrogen phosphate is added at a temperature of 55° C., the molar ratio of bisphenol A epoxy resin to di(methacryloyloxyethyl) hydrogen phosphate is 1:2, and the reaction is carried out at a temperature of 75° C. for 4.5 hours. After the reaction is completed, phosphorus-containing epoxy acrylate is obtained;
[0072] Phosphorus-containing epoxy acrylate, methyl gallate acrylate, active diluent and photoinitiator are uniformly mixed, and hydrotalcite / block copolymer composite material is added, and ultrasonic dispersion is performed at 45° C. for 25 minutes to obtain a weather-resistant and high-strength anticorrosion and rust remover based on an inorganic composite material;
[0073] The mass ratio of phosphorus-containing epoxy acrylate, methyl gallate acrylate, reactive diluent, photoinitiator, and hydrotalcite / block copolymer composite material is 73:5.5:18:3.5:4.5;
[0074] Methyl gallate of acrylic acid is prepared by the following steps:
[0075] Methyl gallate, triethylamine and acetone were mixed and dissolved in a mass ratio of 3.6:0.5:45, and acryloyl chloride was added dropwise in a nitrogen atmosphere at 0°C, the molar ratio of methyl gallate to acryloyl chloride was 1:1.05, and the dropping time was 25 min. After the dropping was completed, the temperature was raised to 35°C and the reaction was carried out for 5.5 h. After the reaction was completed, the filtrate was filtered and the solvent acetone was removed by rotary evaporation at 30°C to obtain a crude reaction product. 0°C water with an amount 5 times the mass of the crude reaction product was added for washing, and the product was dried at 50°C for 12 h to obtain methyl gallate of acrylic acid.
[0076] Example 4
[0077] This embodiment discloses a method for preparing a weather-resistant high-strength anticorrosion and rust remover based on an inorganic composite material, comprising the following steps:
[0078] Step (1), preparing a hydrotalcite / block copolymer composite material;
[0079] S11, thieno[3,4-B]-1,4-dioxin-2-methanol, tetrahydrofuran, and sodium hydride were mixed in a nitrogen atmosphere at a mass ratio of 6.28:55:2.2, 1,4-di(bromomethyl)benzene was added, and the molar ratio of thieno[3,4-B]-1,4-dioxin-2-methanol to 1,4-di(bromomethyl)benzene was 1:1.2, and the mixture was reacted at a set temperature of 70°C for 9 hours. After the reaction was completed, the mixture was cooled to room temperature to obtain a reaction product, and ethyl acetate and water in an amount 3 times the mass of the reaction product were added in sequence for extraction, the organic phase was taken, 20 wt% of anhydrous magnesium sulfate was added to the organic phase for drying and dehydration, the organic phase was filtered, the filtrate was taken, the solvent ethyl acetate was removed by rotary evaporation at 50°C, and the thiophene-containing initiator was obtained by column chromatography;
[0080] The eluent used in column chromatography separation was prepared by mixing n-hexane and ethyl acetate in a volume ratio of 10:1;
[0081] S12, mixing acrylic acid, hydrotalcite and dimethyl sulfoxide in a mass ratio of 2.8:10:120, and ultrasonically dispersing for 10 minutes to obtain a hydrotalcite dispersion;
[0082] Cuprous bromide, pentamethyldiethylenetriamine, styrene and dimethyl sulfoxide were mixed evenly, reacted in a nitrogen atmosphere at 85°C, and after the reaction was completed, a hydrotalcite dispersion and a thiophene-containing initiator were added, and the reaction was continued for 2 hours in a nitrogen atmosphere at 85°C. After the reaction was completed, a crude reaction product was obtained, methanol 5 times the mass of the crude reaction product was added, and the mixture was allowed to stand for 10 minutes, filtered, and the filter cake was taken, and dichloromethane 5 times the mass of the filter cake and water were added in turn for washing, and dried at 50°C for 18 hours to obtain a hydrotalcite / block copolymer composite material;
[0083] The mass ratio of cuprous bromide, pentamethyldiethylenetriamine, styrene, dimethyl sulfoxide, hydrotalcite dispersion, and thiophene-containing initiator is 0.58:0.68:5.5:48:255:5.5;
[0084] Step (2), bisphenol A epoxy resin, hydroquinone, and tetraethylammonium bromide are uniformly mixed in a mass ratio of 100:0.03:0.5, di(methacryloyloxyethyl) hydrogen phosphate is added at a temperature of 55° C., the molar ratio of bisphenol A epoxy resin to di(methacryloyloxyethyl) hydrogen phosphate is 1:2, and the reaction is carried out at a temperature of 75° C. for 4.5 hours. After the reaction is completed, phosphorus-containing epoxy acrylate is obtained;
[0085] Phosphorus-containing epoxy acrylate, methyl gallate acrylate, active diluent and photoinitiator are uniformly mixed, and hydrotalcite / block copolymer composite material is added, and ultrasonic dispersion is performed at 50° C. for 25 minutes to obtain a weather-resistant and high-strength anticorrosion and rust remover based on an inorganic composite material;
[0086] The mass ratio of phosphorus-containing epoxy acrylate, methyl gallate acrylate, reactive diluent, photoinitiator, and hydrotalcite / block copolymer composite material is 74:5.8:19:3.5:4.8;
[0087] Methyl gallate of acrylic acid is prepared by the following steps:
[0088] Methyl gallate, triethylamine and acetone were mixed and dissolved in a mass ratio of 3.65:0.5:45, and acryloyl chloride was added dropwise in a nitrogen atmosphere at 0°C, the molar ratio of methyl gallate to acryloyl chloride was 1:1.05, and the dropping time was 25 min. After the dropping was completed, the temperature was raised to 35°C and the reaction was carried out for 5.5 h. After the reaction was completed, the filtrate was filtered and the solvent acetone was removed by rotary evaporation at 30°C to obtain a crude reaction product. 0°C water with an amount 5 times the mass of the crude reaction product was added for washing, and the product was dried at 50°C for 12 h to obtain methyl gallate of acrylic acid.
[0089] Example 5
[0090] This embodiment discloses a method for preparing a weather-resistant high-strength anticorrosion and rust remover based on an inorganic composite material, comprising the following steps:
[0091] Step (1), preparing a hydrotalcite / block copolymer composite material;
[0092] S11, thieno[3,4-B]-1,4-dioxin-2-methanol, tetrahydrofuran, and sodium hydride were mixed in a nitrogen atmosphere at a mass ratio of 6.3:60:2.2, 1,4-di(bromomethyl)benzene was added, and the molar ratio of thieno[3,4-B]-1,4-dioxin-2-methanol to 1,4-di(bromomethyl)benzene was 1:1.2, and the mixture was reacted at a set temperature of 75°C for 8 hours. After the reaction was completed, the mixture was cooled to room temperature to obtain a reaction product, and ethyl acetate and water in an amount of 4 times the mass of the reaction product were added in sequence for extraction, the organic phase was taken, 20 wt% of anhydrous magnesium sulfate was added to the organic phase for drying and dehydration, the organic phase was filtered, the filtrate was taken, the solvent ethyl acetate was removed by rotary evaporation at 60°C, and the thiophene-containing initiator was obtained by column chromatography;
[0093] The eluent used in column chromatography separation was prepared by mixing n-hexane and ethyl acetate in a volume ratio of 10:1;
[0094] S12, mixing acrylic acid, hydrotalcite and dimethyl sulfoxide in a mass ratio of 3:10:130, and ultrasonically dispersing for 20 minutes to obtain a hydrotalcite dispersion;
[0095] Cuprous bromide, pentamethyldiethylenetriamine, styrene and dimethyl sulfoxide were mixed evenly, reacted in a nitrogen atmosphere at 85°C, and after the reaction was completed, a hydrotalcite dispersion and a thiophene-containing initiator were added, and the reaction was continued for 2 hours in a nitrogen atmosphere at 85°C. After the reaction was completed, a crude reaction product was obtained, methanol 6 times the mass of the crude reaction product was added, and the mixture was allowed to stand for 15 minutes, filtered, and the filter cake was taken. Dichloromethane 6 times the mass of the filter cake and water were added in turn for washing, and the mixture was dried at 60°C for 12 hours to obtain a hydrotalcite / block copolymer composite material;
[0096] The mass ratio of cuprous bromide, pentamethyldiethylenetriamine, styrene, dimethyl sulfoxide, hydrotalcite dispersion, and thiophene-containing initiator is 0.6:0.7:6:50:260:6;
[0097] Step (2), bisphenol A epoxy resin, hydroquinone, and tetraethylammonium bromide are uniformly mixed in a mass ratio of 100:0.03:0.5, di(methacryloyloxyethyl) hydrogen phosphate is added at a temperature of 60° C., the molar ratio of bisphenol A epoxy resin to di(methacryloyloxyethyl) hydrogen phosphate is 1:2, and the reaction is carried out at a temperature of 80° C. for 4 hours. After the reaction is completed, phosphorus-containing epoxy acrylate is obtained;
[0098] Phosphorus-containing epoxy acrylate, methyl gallate of acrylate, active diluent and photoinitiator are uniformly mixed, and hydrotalcite / block copolymer composite material is added, and ultrasonic dispersion is performed at 50° C. for 20 minutes to obtain a weather-resistant and high-strength anticorrosion and rust remover based on an inorganic composite material;
[0099] The mass ratio of phosphorus-containing epoxy acrylate, methyl gallate acrylate, reactive diluent, photoinitiator, and hydrotalcite / block copolymer composite material is 75:6:20:4:5;
[0100] Methyl gallate of acrylic acid is prepared by the following steps:
[0101] Methyl gallate, triethylamine and acetone were mixed and dissolved in a mass ratio of 3.7:0.5:50, and acryloyl chloride was added dropwise in a nitrogen atmosphere at 2°C, the molar ratio of methyl gallate to acryloyl chloride was 1:1.1, and the dropping time was 30 min. After the dropping was completed, the temperature was raised to 35°C and reacted for 5 h. After the reaction was completed, the filtrate was filtered and the solvent acetone was removed by rotary evaporation at 40°C to obtain a crude reaction product. 8 times the mass of the crude reaction product was added with 0°C water for washing, and dried at 60°C for 10 h to obtain methyl gallate of acrylic acid.
[0102] Comparative Example 1
[0103] This comparative example discloses a method for preparing a rust remover, comprising the following steps:
[0104] Bisphenol A epoxy resin, hydroquinone, and tetraethylammonium bromide are uniformly mixed in a mass ratio of 100:0.025:0.4, di(methacryloyloxyethyl) hydrogen phosphate is added at a temperature of 50° C., the molar ratio of bisphenol A epoxy resin to di(methacryloyloxyethyl) hydrogen phosphate is 1:2, and the mixture is reacted at a temperature of 70° C. for 5 hours. After the reaction is completed, phosphorus-containing epoxy acrylate is obtained;
[0105] Phosphorus-containing epoxy acrylate, methyl gallate acrylate, reactive diluent and photoinitiator are uniformly mixed, and ultrasonically dispersed at 40° C. for 30 minutes to obtain a rust remover;
[0106] Among them, the mass ratio of phosphorus-containing epoxy acrylate, methyl gallate acrylate, reactive diluent, and photoinitiator is 70:5:15:3;
[0107] Methyl gallate of acrylic acid is prepared by the following steps:
[0108] Methyl gallate, triethylamine and acetone were mixed and dissolved in a mass ratio of 3.5:0.5:40, and acryloyl chloride was added dropwise in a nitrogen atmosphere at 0°C, the molar ratio of methyl gallate to acryloyl chloride was 1:1, and the dropping time was 20 min. After the dropping was completed, the temperature was raised to 35°C and reacted for 6 h. After the reaction was completed, the filtrate was filtered and the solvent acetone was removed by rotary evaporation at 30°C to obtain a crude reaction product. 0°C water with an amount 5 times the mass of the crude reaction product was added for washing, and the product was dried at 50°C for 12 h to obtain methyl gallate of acrylic acid.
[0109] Comparative Example 2
[0110] This comparative example discloses a method for preparing a rust remover, comprising the following steps:
[0111] Bisphenol A epoxy resin, hydroquinone, and tetraethylammonium bromide are uniformly mixed in a mass ratio of 100:0.025:0.4, di(methacryloyloxyethyl) hydrogen phosphate is added at a temperature of 50° C., the molar ratio of bisphenol A epoxy resin to di(methacryloyloxyethyl) hydrogen phosphate is 1:2, and the mixture is reacted at a temperature of 70° C. for 5 hours. After the reaction is completed, phosphorus-containing epoxy acrylate is obtained;
[0112] Phosphorus-containing epoxy acrylate, methyl gallate acrylate, reactive diluent and photoinitiator were uniformly mixed, hydrotalcite was added, and ultrasonic dispersion was performed at 40° C. for 30 minutes to obtain a rust remover;
[0113] The mass ratio of phosphorus-containing epoxy acrylate, methyl gallate acrylate, reactive diluent, photoinitiator and hydrotalcite is 70:5:15:3:4;
[0114] Methyl gallate of acrylic acid is prepared by the following steps:
[0115] Methyl gallate, triethylamine and acetone were mixed and dissolved in a mass ratio of 3.5:0.5:40, and acryloyl chloride was added dropwise in a nitrogen atmosphere at 0°C, the molar ratio of methyl gallate to acryloyl chloride was 1:1, and the dropping time was 20 min. After the dropping was completed, the temperature was raised to 35°C and reacted for 6 h. After the reaction was completed, the filtrate was filtered and the solvent acetone was removed by rotary evaporation at 30°C to obtain a crude reaction product. 0°C water with an amount 5 times the mass of the crude reaction product was added for washing, and the product was dried at 50°C for 12 h to obtain methyl gallate of acrylic acid.
[0116] Comparative Example 3
[0117] This comparative example discloses a method for preparing a rust remover, comprising the following steps:
[0118] Step (1), preparing a hydrotalcite / block copolymer composite material;
[0119] S11, thieno[3,4-B]-1,4-dioxin-2-methanol, tetrahydrofuran, and sodium hydride were mixed in a nitrogen atmosphere at a mass ratio of 6.2:50:2.1, 1,4-di(bromomethyl)benzene was added, and the molar ratio of thieno[3,4-B]-1,4-dioxin-2-methanol to 1,4-di(bromomethyl)benzene was 1:1.1, and the reaction was carried out at a set temperature of 65°C for 10 hours. After the reaction was completed, the reaction was cooled to room temperature to obtain a reaction product, and ethyl acetate and water in an amount of 3 times the mass of the reaction product were added in sequence for extraction, the organic phase was taken, 20 wt% of anhydrous magnesium sulfate was added to the organic phase for drying and dehydration, the organic phase was filtered, the filtrate was taken, the solvent ethyl acetate was removed by rotary evaporation at 50°C, and the thiophene-containing initiator was obtained;
[0120] The eluent used in column chromatography separation was prepared by mixing n-hexane and ethyl acetate in a volume ratio of 10:1;
[0121] S12, mixing acrylic acid, hydrotalcite and dimethyl sulfoxide in a mass ratio of 2:10:100, and ultrasonically dispersing for 10 minutes to obtain a hydrotalcite dispersion;
[0122] Cuprous bromide, pentamethyldiethylenetriamine, styrene and dimethyl sulfoxide were mixed evenly, reacted in a nitrogen atmosphere at 80°C, and after the reaction was completed, a hydrotalcite dispersion and a thiophene-containing initiator were added, and the reaction was continued for 3 hours in a nitrogen atmosphere at 80°C. After the reaction was completed, a crude reaction product was obtained, methanol 5 times the mass of the crude reaction product was added, and the mixture was allowed to stand for 10 minutes, filtered, and the filter cake was taken. Dichloromethane 5 times the mass of the filter cake and water were added in turn for washing, and the mixture was dried at 50°C for 18 hours to obtain a hydrotalcite / block copolymer composite material;
[0123] The mass ratio of cuprous bromide, pentamethyldiethylenetriamine, styrene, dimethyl sulfoxide, hydrotalcite dispersion, and thiophene-containing initiator is 0.5:0.6:4:45:240:4;
[0124] Step (2), bisphenol A epoxy resin, hydroquinone, and tetraethylammonium bromide are uniformly mixed in a mass ratio of 100:0.025:0.4, di(methacryloyloxyethyl) hydrogen phosphate is added at a temperature of 50° C., the molar ratio of bisphenol A epoxy resin to di(methacryloyloxyethyl) hydrogen phosphate is 1:2, and the reaction is carried out at a temperature of 70° C. for 5 hours. After the reaction is completed, phosphorus-containing epoxy acrylate is obtained;
[0125] Phosphorus-containing epoxy acrylate, methyl acrylate, reactive diluent and photoinitiator are uniformly mixed, and the hydrotalcite / block copolymer composite material is added, and ultrasonic dispersion is performed at a temperature of 40° C. for 30 minutes to obtain a rust remover;
[0126] The mass ratio of phosphorus-containing epoxy acrylate, methyl acrylate, active diluent, photoinitiator, and hydrotalcite / block copolymer composite material is 70:5:15:3:4.
[0127] In the above embodiments and comparative examples:
[0128] Thieno[3,4-B]-1,4-dioxol-2-methanol was obtained from Shanghai Aladdin Biochemical Technology Co., Ltd., CAS No.: 146796-02-3; 1,4-di(bromomethyl)benzene was obtained from AlfaAesar, CAS No.: 623-24-5; hydrotalcite was obtained from Hefei Anyuhe New Materials Technology Co., Ltd., product name: magnesium aluminum hydrotalcite, magnesium aluminum molar ratio of 2-2.3, average particle size 1 μm; bisphenol A epoxy resin was obtained from Chengdu Jingyi New Materials Co., Ltd., product name: Phoenix brand bisphenol A epoxy resin E44; di(methacryloyloxyethyl) hydrogen phosphate was obtained from Sigma-Aldrich , CAS number: 32435-46-4; methyl gallate is from Shanghai Shaoyuan Reagent Co., Ltd., CAS number: 99-24-1; acryloyl chloride is from Shanghai Aladdin Biochemical Technology Co., Ltd., CAS number: 814-68-6; the photoinitiator is prepared by mixing photoinitiator 1173 and photoinitiator 2959 in a mass ratio of 1:1, and photoinitiator 1173 and photoinitiator 2959 are both commercially available; the active diluent is prepared by mixing trimethylolpropane triacrylate and tripropylene glycol diacrylate in a mass ratio of 2:3, and trimethylolpropane triacrylate and tripropylene glycol diacrylate are both commercially available.
[0129] Test example
[0130] The rust removers prepared in Examples 1-5 and Comparative Examples 1-3 were coated on a common rusted A3 carbon steel sheet with a size of 40 mm×13 mm×1.5 mm that had been polished and had obvious floating rust removed, and irradiated and cured for 10 minutes in ultraviolet light with a wavelength of 365 nm. After the curing was completed, samples 1-8 with an average film thickness of 60 μm were obtained respectively. The performance of samples 1-8 was tested, and the specific test results are shown in Table 1:
[0131] Table 1
[0132]
[0133]
[0134] The detection of each indicator in Table 1 is based on the following standards:
[0135] The adhesion is determined by referring to GB / T9286-2021 "Scratch test for paint and varnish films"; the hardness is determined by referring to GB / T6739-2006 "Determination of paint film hardness by pencil method for paint and varnish"; the impact strength is determined by referring to GB / T1732-2020 "Determination of impact resistance of paint films"; the salt spray resistance is determined by referring to GB / T1771-1991 "Determination of neutral salt spray resistance of paints and varnishes"; the artificial weathering resistance is determined by referring to GB / T14522 "Artificial weathering test method for rubber, coatings and rubber materials for mechanical industrial products - fluorescent ultraviolet lamp"; the alkali resistance is determined by referring to GB / T 1763-1989 "Determination of chemical resistance of paint films", and the alkali solution is a saturated calcium hydroxide aqueous solution.
[0136] It can be seen from the test results in Table 1 that the coating formed by the rust remover prepared by the present invention after coating and curing has high mechanical strength and durable weather resistance and corrosion resistance.
[0137] The hydrotalcite / block copolymer composite material of the present invention can form coordination bonds with iron ions in rust and iron on the surface of iron-containing metal substrates by utilizing lone pairs of electrons due to the heterocyclic structure containing thiophene groups, and can be used as a corrosion inhibitor to give the coating matrix excellent anti-corrosion performance. In addition, hydrotalcite, as an inorganic reinforcing filler, has a layered structure and excellent ultraviolet absorption performance. The maze effect existing when the hydrotalcite is dispersed in the coating increases the diffusion path of the corrosive medium to the metal surface, prolongs the corrosion resistance time, and further improves the anti-corrosion performance of the coating. At the same time, the ultraviolet light aging resistance, weather resistance and mechanical properties of the coating are also improved.
[0138] No hydrotalcite / block copolymer composite material was added in Comparative Example 1. Due to the lack of a heterocyclic structure of a thiophene group as a corrosion inhibitor, and the lack of hydrotalcite with a layered structure and an ultraviolet absorber as an inorganic reinforcing material, the hardness and impact strength of Sample 6 prepared in Comparative Example 1 were reduced, and its corrosion resistance and weather resistance were inferior to those of the embodiments.
[0139] In Comparative Example 2, the hydrotalcite has no surface modification, the dispersibility and compatibility of the inorganic filler hydrotalcite in the matrix are reduced, and it is easy to agglomerate, which affects the mechanical properties of the film after coating. In addition, the heterocyclic structure of the thiophene group is lacking as a corrosion inhibitor, so the mechanical properties and corrosion resistance of Sample 7 prepared in Comparative Example 2 are both reduced.
[0140] While participating in the photocuring of the matrix resin, methyl acrylate gallate can utilize the strong chelating ability of phenolic hydroxyl group and iron ions to form a structurally stable complex, which plays the role of rust conversion, shielding, and corrosion inhibition as a rust conversion agent, thereby improving the anti-corrosion performance of the coating. In Comparative Example 3, methyl acrylate gallate is replaced by methyl acrylate, which lacks the effect of methyl acrylate gallate as a rust conversion agent to improve the anti-corrosion performance of the coating, so the anti-corrosion performance of Sample 8 prepared by Comparative Example 3 is reduced.
[0141] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a weather-resistant high-strength anticorrosion and rust remover based on an inorganic composite material, characterized in that: The following steps are involved: Step (1), mixing cuprous bromide, pentamethyldiethylenetriamine, styrene and dimethyl sulfoxide evenly, reacting, adding a hydrotalcite dispersion and a thiophene-containing initiator after the reaction is completed, continuing the reaction, purifying after the reaction is completed, and obtaining a hydrotalcite / block copolymer composite material; Step (2), uniformly mixing phosphorus-containing epoxy acrylate, methyl acrylate gallate, active diluent and photoinitiator, adding hydrotalcite / block copolymer composite material, and ultrasonically dispersing to obtain a weather-resistant high-strength anticorrosion and rust remover based on inorganic composite material.
2. The method for preparing a weather-resistant high-strength anticorrosion and rust remover based on an inorganic composite material according to claim 1, characterized in that: The step (1): the mass ratio of cuprous bromide, pentamethyldiethylenetriamine, styrene, dimethyl sulfoxide, hydrotalcite dispersion, and thiophene-containing initiator is 0.5-0.6:0.6-0.7:4-6:45-50:240-260:4-6; the reaction conditions are: reacting in a nitrogen atmosphere at a temperature of 80-85° C.; the continued reaction conditions are: continuing the reaction in a nitrogen atmosphere at a temperature of 80-85° C. for 2-3 hours.
3. The method for preparing a weather-resistant high-strength anticorrosion and rust remover based on an inorganic composite material according to claim 1, characterized in that: The hydrotalcite dispersion in step (1) is prepared by mixing acrylic acid, hydrotalcite and dimethyl sulfoxide in a mass ratio of 2-3:10:100-130, and performing ultrasonic dispersion to obtain a hydrotalcite dispersion.
4. The method for preparing a weather-resistant high-strength anticorrosion and rust remover based on an inorganic composite material according to claim 1, characterized in that: In the step (1), the thiophene-containing initiator is prepared by the following steps: Thieno[3,4-B]-1,4-dioxin-2-methanol, tetrahydrofuran and sodium hydride are uniformly mixed, 1,4-di(bromomethyl)benzene is added, and the mixture is reacted. After the reaction is completed, the mixture is cooled and purified to obtain a thiophene-containing initiator; Among them, the mass ratio of thieno[3,4-B]-1,4-dioxin-2-methanol, tetrahydrofuran and sodium hydride is 6.2-6.3:50-60:2.1-2.2; the molar ratio of thieno[3,4-B]-1,4-dioxin-2-methanol and 1,4-di(bromomethyl)benzene is 1:1.1-1.2; the reaction conditions are: in a nitrogen atmosphere, the reaction temperature is set at 65-75°C for 8-10 hours.
5. The method for preparing a weather-resistant high-strength anticorrosion and rust remover based on an inorganic composite material according to claim 1, characterized in that: In the step (2), the phosphorus-containing epoxy acrylate is prepared by the following steps: Bisphenol A epoxy resin, hydroquinone and tetraethylammonium bromide are uniformly mixed, di(methacryloyloxyethyl) hydrogen phosphate is added, and reacted. After the reaction is completed, phosphorus-containing epoxy acrylate is obtained; Among them, the mass ratio of bisphenol A epoxy resin, hydroquinone and tetraethylammonium bromide is 100:0.025-0.03:0.4-0.5; the molar ratio of bisphenol A epoxy resin and di(methacryloyloxyethyl) hydrogen phosphate is 1:2; and the reaction conditions are: react at a temperature of 70-80°C for 4-5h.
6. The method for preparing a weather-resistant high-strength anticorrosion and rust remover based on an inorganic composite material according to claim 1, characterized in that: In the step (2), the mass ratio of phosphorus-containing epoxy acrylate, methyl gallate acrylate, reactive diluent, photoinitiator, and hydrotalcite / block copolymer composite material is 70-75:5-6:15-20:3-4:4-5.
7. The method for preparing a weather-resistant high-strength anticorrosion and rust remover based on an inorganic composite material according to claim 1, characterized in that: In the step (2), methyl gallate of acrylic acid is prepared by the following steps: Methyl gallate, triethylamine and acetone are mixed and dissolved, and acryloyl chloride is added dropwise. After the addition is completed, the temperature is increased and the reaction is carried out. After the reaction is completed, the mixture is filtered and purified to obtain methyl gallate of acrylic acid.
8. The method for preparing a weather-resistant high-strength anticorrosion and rust remover based on an inorganic composite material according to claim 7, characterized in that: In the preparation of methyl gallate of acrylic acid, the mass ratio of methyl gallate, triethylamine and acetone is 3.5-3.7:0.5:40-50; the molar ratio of methyl gallate to acryloyl chloride is 1:1-1.1; the dripping condition of acryloyl chloride is: dripping for 20-30 minutes at a temperature of 0-2° C. in a nitrogen atmosphere; and the reaction condition is: reacting at a temperature of 35-40° C. for 5-6 hours.
9. A weather-resistant and high-strength anti-corrosion and rust-removing agent based on an inorganic composite material prepared by the preparation method of the weather-resistant and high-strength anti-corrosion and rust-removing agent based on an inorganic composite material as described in any one of claims 1 to 8.
10. Use of the weather-resistant, high-strength anti-corrosion and rust-removing agent based on inorganic composite materials as claimed in claim 9 on bolts.
Citation Information
Patent Citations
Conversion type aqueous rust coating and preparation method thereof
CN109181452A
Cited By
High-weather-resistance quick-drying coating as well as preparation method and application thereof
CN121108861A